Sultr4;1 mutant seeds of Arabidopsis have an enhanced sulphate content and modified proteome suggesting metabolic adaptations to altered sulphate compartmentalization - Zuber, Hélène; Wirtz, Markus; Hell, Rüdiger (BMC plant biology, 2010)
Sulphur is an essential macronutrient needed for the synthesis of many cellular components. Sulphur containing amino acids and stress response-related compounds, such as glutathione, are derived from reduction of root-absorbed sulphate. Sulphate distribution in cell compartments necessitates specific transport systems. The low-affinity sulphate transporters SULTR4;1 and SULTR4;2 have been localized to the vacuolar membrane, where they may facilitate sulphate efflux from the vacuole.